Ct Findings of Giant Gastric Leiomyosarcomas - Akmangit, İlkay; Lakadamyalı, Hatice (Fırat University, 2002)
Leiomyosarcomas compose of 1-3% of malignant gastric tumors. Computed tomography (CT) can evaluate localisation of the lesion, relations with related organs and distant organ metastasis. CT scans of leiomyosarcomas are painted in heterogenous manner after intravenous contrast media injection and visualised as masses greater than five cm which contain cavitations and necrotic areas. In this article we compared the CT results of a giant gastric leiomyosarcoma with literature.

Malign mide tümörlerinin % 1-3'ünü leyomiyosarkomlar oluştururlar. Bilgisayarlı tomografi (BT) ile lezyonun lokalizasyonu, özellikleri, komşu dokular ile olan ilişkileri, uzak organ metastazları başarıyla gösterilebilir. Leyomiyosarkomlar BT'de intravenöz kontrast madde verilmesi sonrası heterojen paternde boyanan, içerisinde yer yer kavitasyon ve nekroz alanları bulunan, beş cm'den büyük kitleler şeklinde izlenirler. Biz de bu yazıda dev mide leyomiyosarkomu olan hastanın BT bulgularını literatürdeki bulgularla karşılaştırdık.
Dev Mide Leiomyosarkomunda Bt Bulguları